Chapter Il territorio pontino nei disegni di Leonardo da Vinci - CARNEVALI, Laura (Territori, 2023)
The Pontine territory, located in southern Lazio, once ʽpalus pontinaʼ, has been represented over the centuries through iconographic views, cartographic drawings, literary documentation, and designed through reclamation works that allowed, over time, to dry up and anthropize the land. The two moments of representation and design of the Pontine territory are clearly reflected in Leonardo's Cartographic view of the Pontine plain and the coast north of Terracina, of which the paper presents a critical reading.